The influence of dapagliflozin on cardiac remodeling, myocardial function and metabolomics in type 1 diabetes mellitus rats - Eder Anderson Rodrigues; Camila Moreno Rosa; Dijon Henrique Salome Campos; Felipe Cesar Damatto; Gilson Masahiro Murata; Lidiane Moreira Souza; Luana Urbano Pagan; Mariana Gatto; Jessica Yumi Brosler; Hebreia Oliveira Almeida Souza; Mario Machado Martins; Luciana Machado Bastos; et al. (Diabetology & Metabolic Syndrome, 2023)
Abstract Background Sodium-glucose cotransporter (SGLT)2 inhibitors have displayed beneficial effects on the cardiovascular system in diabetes mellitus (DM) patients. As most clinical trials were performed in Type 2 DM, their effects in Type 1 DM have not been established. Objective To evaluate the influence of long-term treatment with SGLT2 inhibitor dapagliflozin on cardiac remodeling, myocardial function, energy metabolism, and metabolomics in rats with Type 1 DM. Methods Male Wistar rats were divided into groups: Control (C, n = 15); DM (n = 15); and DM treated with dapagliflozin (DM + DAPA, n = 15) for 30 weeks. DM was induced by streptozotocin. Dapagliflozin 5 mg/kg/day was added to chow. Statistical analysis: ANOVA and Tukey or Kruskal-Wallis and Dunn. Results DM + DAPA presented lower glycemia and higher body weight than DM. Echocardiogram showed DM with left atrium dilation and left ventricular (LV) hypertrophy, dilation, and systolic and diastolic dysfunction. In LV isolated papillary muscles, DM had reduced developed tension, +dT/dt and -dT/dt in basal condition and after inotropic stimulation. All functional changes were attenuated by dapagliflozin. Hexokinase (HK), phosphofructokinase (PFK) and pyruvate kinase (PK) activity was lower in DM than C, and PFK and PK activity higher in DM + DAPA than DM. Metabolomics revealed 21 and 5 metabolites positively regulated in DM vs. C and DM + DAPA vs. DM, respectively; 6 and 3 metabolites were negatively regulated in DM vs. C and DM + DAPA vs. DM, respectively. Five metabolites that participate in cell membrane ultrastructure were higher in DM than C. Metabolites levels of N-oleoyl glutamic acid, chlorocresol and N-oleoyl-L-serine were lower and phosphatidylethanolamine and ceramide higher in DM + DAPA than DM. Conclusion Long-term treatment with dapagliflozin attenuates cardiac remodeling, myocardial dysfunction, and contractile reserve impairment in Type 1 diabetic rats. The functional improvement is combined with restored pyruvate kinase and phosphofructokinase activity and attenuated metabolomics changes.